2003
DOI: 10.1046/j.1365-2826.2003.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin‐Releasing Hormone Immunoreactivity in Human T and B Cells and Macrophages: Colocalization With Arginine Vasopressin

Abstract: Corticotropin-releasing hormone (CRH) and arginine vasopressin (AVP) are expressed in cells of the immune system where they exert immunomodulatory roles, but these neuropeptides are poorly characterized in human immune tissues. The aim of this study was to determine concentrations and distribution of CRH and AVP in nonactivated human peripheral blood mononuclear cells (PBMC). PBMC from normal human subjects were separated into enriched subpopulations of T and B cells and monocytes/macrophages by a magnetic bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 46 publications
0
41
0
1
Order By: Relevance
“…Vasopressin is expressed in peripheral mononuclear cells including T cells, B cells and monocytes/macrophages [74] . Interestingly, it is co-localized with CRF in T cells, B cells and monocytes/macrophages [75] . Vasopressin is also found in human thymic epithelial cells [76] and in B cells of the spleen [77] .…”
Section: Inflammatory and Immune Effects Of Vasopressinmentioning
confidence: 99%
“…Vasopressin is expressed in peripheral mononuclear cells including T cells, B cells and monocytes/macrophages [74] . Interestingly, it is co-localized with CRF in T cells, B cells and monocytes/macrophages [75] . Vasopressin is also found in human thymic epithelial cells [76] and in B cells of the spleen [77] .…”
Section: Inflammatory and Immune Effects Of Vasopressinmentioning
confidence: 99%
“…Corticotropin-releasing hormone (CRH) is mainly localized in the brain [1,2], and can also be detected in peripheral tissues including the gut [3,4,5] and immune cells and organs [6,7,8] in experimental animals and humans [9,10,11]. Although these tissues can be potential sources of circulating CRH, earlier studies have indicated that CRH levels are either nondetectable in rats or low in human plasma [12] as assessed by radioimmunoassay (RIA).…”
Section: Introductionmentioning
confidence: 99%
“…34,35 CRH, the central mediator of the stress hormone system, has additional peripheral roles in the gastrointestinal tract, cardiovascular system, and skin. 36 CRH also has immunoreactivity and other functions in T cells in human subjects, [37][38][39] but it has yet to be directly proved that human T cells express CRHRs. Thus we first confirmed that circulating T cells expressed CRHR1/ CRHR2 protein and mRNA and that infiltrated T cells in AD skin expressed CRHR1/CRHR2 protein.…”
Section: Discussionmentioning
confidence: 99%